The Association Between Lentiform Nucleus Function and Cognitive Impairments in Schizophrenia - Li, Ping; Zhao, Shu-Wan; Wu, Xu-Sha; Zhang, Ya-Juan; Song, Lei; Wu, Lin; Liu, Xiao-Fan; Fu, Yu-Fei; Wu, Di; Wu, Wen-Jun; Zhang, Ya-Hong; Yin, Hong; et al. (Frontiers in Human Neuroscience, 2021)
Introduction: Cognitive decline is the core schizophrenia symptom, which is now well accepted. Holding a role in various aspects of cognition, the lentiform nucleus (putamen and globus pallidus) dysfunction contributes to the psychopathology of this disease. However, the effects of lentiform nucleus function on cognitive impairments in schizophrenia are yet to be investigated. Objects: We aim to detect fractional amplitude of low-frequency fluctuation (fALFF) alterations in patients with schizophrenia, and examine their behavioral correlates in relation to cognitive impairments in patients. Methods: All participants underwent magnetic resonance imaging (MRI) and cognitive assessment (digit span and digit symbol coding test). Screening of brain regions with significant changes in fALFF values based on whole brain analysis. Data were analyzed between Jun 2020 and Mar 2021. There was no intervention in addition to routine therapy determined by their clinicians on the basis of standard clinical practice. Results: 136 patients (75 men and 61 women, 24.1 ± 7.4 years old) and 146 healthy controls (82 men and 64 women, 24.2 ± 5.2 years old) involved in the experiments seriatim. Patients with schizophrenia exhibited decreased raw scores of cognitive tests (p < 0.001) and increased fALFF in the bilateral lentiform nuclei (left: 67 voxels; x = −24, y = −6, z = 3; peak t value = 6.9; right: 16 voxels; x = 18, y = 0, z = 3; peak t value = 6.36). fALFF values in the bilateral lentiform nuclei were positively correlated with digit span-backward test scores (left: r = 0.193, p = 0.027; right: r = 0.190, p = 0.030), and the right lentiform nucleus was positively correlated with digit symbol coding scores (r = 0.209, p = 0.016). Conclusions: This study demonstrates that cognitive impairments in schizophrenia are associated with lentiform nucleus activation revealed by MRI, involving working memory and processing speed.